THEORETICAL AND PEDAGOGICAL FOUNDATIONS FOR THE DEVELOPING STUDENTS’ COMPOSITIONAL THINKING - Karshiboyeva, Dilafruz Baxadirovna (SCIENCE and SOCIETY, 2026)
The article analyzes the theoretical and pedagogical foundations for developing students’ compositional thinking in the process of fine arts education. The study highlights the role of the main principles of composition theory – integrity, contrast, ideological unity, and typification in the formation of compositional thinking. The pedagogical conditions that contribute to the development of students’ compositional thinking are also substantiated.